Allowance of Laundry Wastewater Contaminant Parameters by Electrocoagulation Process - Revi Rizky Ramadhan; Peppy Herawati; Hadrah Hadrah (Universitas Nusa Putra, 2023)
The laundry business is one of the household-scale businesses that is currently developing in Jambi City. This is possible because the number of laundry business customers is increasing along with the increase in the population in the city of Jambi and the increasingly diverse activities of the people of the city of Jambi. The laundry business in Jambi City is more than 300 units, so if the laundry waste is not treated first, it will have the potential to cause environmental pollution because of the compounds it contains. This study aims to determine the efficiency of the electrocoagulation process to decrease parameters in laundry wastewater, while the parameters observed are pH, COD (Chemical Oxygen Demand), and Phosphate (PO4). Cause pollution to the surrounding environment, especially in receiving water bodies. Variable voltage (voltage) in the electrocoagulation process is 9 volts, 12 volts, and 15 volts with a reactor capacity of 12 liters with a time of 30 minutes and 60 minutes at each voltage. Decreasing parameters were analyzed by comparing pH, COD (Chemical oxygen demand), and Phosphate (PO4) before and after the study, as well as the effect of voltage (voltage) and contact time on the effectiveness of decreasing parameters. The highest percentage of COD reduction efficiency is 80%, Phosphate Parameter is 92%. Voltage (voltage) and contact time also affect the results of parameter removal.